Developing an Environmental Literacy-Based E-Booklet on Environmental Changes for 10th-Grade Biology Students - Ulil Azmi; Suraida Suraida; Defita Permata Sari; Fadli Emsa Zamani (International Journal of Learning Media on Natural Science (IJLENS), 2025)
Biology learning resources are still largely dominated by thick textbooks that tend to be less engaging, often causing students to feel bored and struggle with understanding the material. This study employed a Research and Development (R&D) design based on the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), but was limited to the Analyze, Design, and Development phases. The purpose of the research was to develop and evaluate the validity and practicality of an environmental literacy-based e-booklet on the topic of environmental changes for 10th-grade students at SMA Islam Al Falah Kota Jambi. Participants consisted of three expert validators, one biology teacher, and 30 students. Data were collected through validation sheets and teacher–student questionnaires. The results indicated an average validation score of 98.82% (very valid) and a practicality score of 92.02% (highly practical). These findings suggest that the developed e-booklet is an appropriate biology learning resource with the potential to enhance students’ environmental awareness, although further testing is needed to evaluate its impact on learning outcomes.